MASS PATTERNS OF HIGHER EDUCATION IN TAMIL NADU - Rajendran; Kumar, Udaya (International Journal of Research -GRANTHAALAYAH, 2016)
Education plays a vital role for economic development of any nation. It reduces social and economic disparities in society. This study explores the public and private higher educational institutions and literacy level of Tamil Nadu. The literacy rate indicates educational level of total population. Education makes and ushers knowledge economy of a country. The importance of educational service is forever growing in the public and private sectors. Education facilitates the acquisition of new technology, skills and knowledge that ultimately increases productivity in rural and urban areas of India. Public and Private partnership institutions play an important role in delivering educational service in the society and itsrole for delivering general and technical educationfor achieving economic development and its producing skill and knowledge of human resource.